Tankyrase Mediates K63-Linked Ubiquitination of JNK to Confer Stress Tolerance and Influence Lifespan in Drosophila. - Li, P.; Huang, P.; Li, X.; Yin, D.; Ma, Z.; Wang, H.; Song, H. (Cell reports, 2018)
Tankyrase (Tnks) transfers poly(ADP-ribose) on substrates. Whereas studies have highlighted the pivotal roles of Tnks in cancer, cherubism, systemic sclerosis, and viral infection, the requirement for Tnks under physiological contexts remains unclear. Here, we report that the loss of Tnks or its muscle-specific knockdown impairs lifespan, stress tolerance, and energy homeostasis in adult Drosophila. We find that Tnks is a positive regulator in the JNK signaling pathway, and modest alterations in the activity of JNK signaling can strengthen or suppress the Tnks mutant phenotypes. We further identify JNK as a direct substrate of Tnks. Although Tnks-dependent poly-ADP-ribosylation is tightly coupled to proteolysis in the proteasome, we demonstrate that Tnks initiates degradation-independent ubiquitination on two lysine residues of JNK to promote its kinase activity and in vivo functions. Our study uncovers a type of posttranslational modification of Tnks substrates and provides insights into Tnks-mediated physiological roles.